THE INFLUENCE OF COMPETENCY ON EMPLOYEE PERFORMANCE AT THE TELKOM SIDENRENG RAPPANG OFFICE - Muhammad Asdar Abdullah; Gazali Amin; Suriadi (Universitas Ichsan Sidenreng Rappang, 2024)
This study aims to determine whether there is an influence between competence on employee performance at the Telkom office of Sidenreng Rappang Regency. The population in this study were all employees at the Telkom office of Sidenreng Rappang Regency, totalling 30 employees, and the sampling technique used was saturated sampling. Data obtained from premiere data and secondary data, data collection techniques used are observation, questionnaires and documentation, the method used in this research is quantitative research methods. Based on the results of the T (Partial) test that has been carried out that Competence (X) with ttihung (3.507) ≥ ttabel (1.998) so that it is proven that the Competency variable has a significant effect on Employee Performance, then at the 5% level of error the hypothesis is stated as H02 rejected and Ha2 accepted. This means that Competence has a significant effect on Employee Performance at the Telkom Sidenreng Rappang Office.